Regional features of changes in winter extreme temperatures and precipitation in Russia in 1970–2015 - T. B. Titkova; E. A. Cherenkova; V. A. Semenov (Лëд и снег, 2018)
Te space-time dynamics of the occurrence of winter extreme events is investigated on the territory of Russia in 1970-2015 on the basis of daily observations at weather stations. It was found that a whole on the territory a noticeable increase in the occurrence of days with extremely high daily temperatures and daily precipitation and a decrease in the occurrence of extremely cold days was noted. Te most noticeable changes happened in the European part of Russia, where at the beginning of the XXI century occurrence of the extremes was greater than during the previous thirty years. Note also that at the beginning of XXI century in Southern Siberia increase of occurrences of both daily maximum and daily minimum temperature was concurrent. Tis combination appears to be caused by the increase in temperature variability in the region due to the alternation of winters with extreme frosts and warmer and wet winters. Te increase in the frequency of extremely high temperatures in the European part of Russia could have been caused by both general warming and the increased inﬂuence of AMO. An increase in the frequency of extreme high and low temperatures in the south of Siberia may be due to the formation of an anticyclonic circulation anomaly with a center near the coast of the Kara Sea, which is responsible for advection of cold air masses from the northeast. As well as cyclonic formation in southern Siberia, along the eastern periphery of which temperate latitudes can receive anomalously warm air from the subtropics.